Pengaruh Religiositas, Prinsip Konsumsi,dan Gaya Hidup Islami Terhadap Keputusan Pembelian Menggunakan Shopee Paylater - Rahmani, Selvi; Mukhsin, Moh; Fakhrudin, Muhamad (Universitas Negeri Surabaya, 2023)
Shopee paylater is currently one of the paylater services that is most in demand by the people of Indonesia. shopee paylater has its own charm because it has a pay later or installment payment method with low interest. This study only focuses on respondents who use the payment method in the next month or pay later and are never late paying shopee paylater bills to avoid usury and provisions in the Islamic religion. The number of samples used in this study was 70, with the criteria of students majoring in Sharia economics using Shopee paylater. Data is collected by spreading questionnaires online and measuring responses on a likert scale. Utilizing data analysis procedures including validity test, reliability test, classic assumption test, multiple regression analysis, and hypothesis test. The results of this study on the religiousity and the principle of each partial consumption significantly affect the buying decision, while the Islamic lifestyle does not significantly affect the buying decision, but on simultaneous trials of religiousity, the principle of consumption and Islamic lifestyle simultaneously affects the buying decision.